Um tear e muitas mãos: o ensino e o uso da leitura em diferentes áreas do conhecimento - Cunha, Marilda Conceição (2023)
It is essential to teach reading to ensure that individuals can learn thoroughly, see themselves in the world, build their own identities and intervene in reality. As a social practice, reading is a right that must be ensured to all, and schools are in charge of teaching it. However, a significant number of students finish school without properly developing reading competence, a situation that can be proven through several assessments. Thus, the main objective of this research is to investigate whether reading is a part of teachers’ practices in different areas of knowledge and what contributions are offered by these teachers to help develop students’ reading competence, given that reading is a learning tool for all areas. Specific objectives are: a) to verify how teachers work with reading in their subjects; b) to identify learning needs of teachers of different areas of knowledge to work with reading in middle school classes; and c) to introduce notes that might contribute to make training proposals. Participants are six teachers of different areas of knowledge who work at a public middle school in the city of São Paulo. Theoretical framework focuses on teaching of reading and teacher training (CINTRA & PASSARELLI, 2012; COLOMER, 2003; 2007; GERALDI, 2004; 2013; IMBERNÓN, 2010; 2011; KLEIMAN & MORAES, 2007; MARCELO GARCÍA, 1999; PETIT, 2008; 2019; SOLÉ, 1998). This qualitative research used semi-structured interviews to build data, given the flexibility of the instrument. Data analysis was based on Lüdke & André (2020), and inspired in Prose Analysis (ANDRÉ, 1983). Results showed it is necessary to improve school-based teacher training to include reading as a teaching object. Public policies should also be created to bring attention to initial and continuous teacher training, so that reading can become a priority as a learning instrument and as an essential object of Knowledge for the development reading competence in different areas of knowledge